الإنترنت وتأثيره على النسق القيمي في المجتمع الليبي (دراسة ميدانية على عينة من طلاب كلية الآداب/ توكرة –جامعة بنغازي) - نجية أحمد الورفلي (Scientific Journal of University of Benghazi, 2020)
The study examined the effect of the Internet on the value structure of the Libyan society. The study included two types of variables representing the independent variable in the use of the Internet, which was measured by the intensity of use and the quality of programs. The dependent variable represented the effect of the Internet on some of the respondents' values ​​of cultural identity and citizenship And social cohesion. The study was based on the sample survey method as a method of collecting the study data by withdrawing it to a representative sample of the study society which amounted to 278 students of the faculty of literature and sciences at Benghazi University. (SPSS) box using the statistical program. The study found that the Internet did not negatively affect the values ​​of Libyan society by testing the hypotheses that showed no relationship between the use of the Internet and the change in the values ​​studied in the study, except for the value of social cohesion, because sitting on the Internet reduced the chances of real communication With family, relatives and friends who, of course, deprived them of meeting, talking and dialogue in all walks of life, as well as enjoying the family atmosphere, which isfull of warmth and emotion.